Infecção por HPV e polimorfismos nos genes TP53 e MDM2 em mulheres HIV positivas e negativas - Entiauspe, Ludmila Gonçalves (2013)
Estimates show that approximately 80% of sexually active women will be infected by the Human Papillomavirus (HPV) in some point of their life course, and HPV DNA has been found in 99,7% of cervical cancer (CC) cases. Thus, several factors may contribute to CC development, including co-infections with Human Immunodeficiency Virus (HIV), as well as genetic factors, including TP53 and MDM2 polymorphisms. Some authors have associated CC development risk, among women infected with oncogenic HPV strains, with the Arg72Pro TP53 SNP. The MDM2 protein plays an important role in p53 protein regulation and, thus, a MDM2 SNP referred as SNP309 may also be implicated in CC risk in association with high-risk HPV genotypes. The present work aimed at determining the frequencies of HPV infection and identification of its genotypes, as well as the frequencies of the SNPs Arg72Pro and SNP309 and their associations with CC risk in female HIV-positive and negative populations in the city of Pelotas. It has been observed a prevalence of HPV infection of 30% among HIV-negative women, and 68% in the positive group. The HPV-16 genotype was the most prevalent in the HIV-negative group, and HPV-6 in the positive group. Among HPV-positive women, the TP53 Arg/Arg genotype was the most prevalent in both HIV groups, and the SNP309 TT genotype was the most prevalent in the HIV negative group, and the TG genotype in the positive group. These findings suggest that future investigations in larger populations are necessary and of interest to better understand the potential roles of these SNPs in HPV infected women.